The Impact of Teleworking and Home Environment on Work Productivity - Fidayan, Abdul; Tri Satya, Mutia (Adpebi International Journal of Multidisciplinary Sciences, 2025)
Purpose – This paper aims to examine the effects of teleworking, home environment, and distractions on work productivity, with a focus on understanding how these factors influence productivity in the context of remote work. Methodology/approach – A survey was conducted with 200 respondents, and interviews were carried out to collect both quantitative and qualitative data, providing comprehensive insights into how teleworking and home environment quality impact productivity, particularly in relation to distractions. Findings – The study found that teleworking significantly enhances productivity, with a well-organized home environment being the most influential factor. Interestingly, minor distractions can improve productivity by providing necessary mental breaks, while excessive digital distractions hinder work performance. Novelty/value – As remote work becomes more widespread, this research contributes to the understanding of the interaction between teleworking, home environment, and distractions, offering valuable insights for businesses seeking to optimize employee productivity in a teleworking setup.